Ideologies of Blackness and the translation of Black African literature in Maoist China: a paratextual exploration - Sherman, Byron B. (My University, 2022)
In the present study, I sketch a translation history of Black literatures in China prior to 1966, and propose that the paratexts to these works may be excavated for insights into the role of Blackness and Africa in the Chinese imaginary and how it impacted the presentation and translation of Black literatures. I show how factors such as the emergent racialized Chinese world view in the early twentieth century, indignation at the treatment of China and its people at home and abroad, conceptions of l literatures during the May Fourth era in the 1920s, the development of a left wing politics in the literary establishment during the 1930s, Soviet-oriented translation policies and anti-US ideologies in the early 1950s, as well as the emphasis on anti-colonialism and Third World solidarity in the early 1960s, impacted the translation and paratextual framings of diasporic Black, and subsequently, Black African literatures. The project reveals a high degree of consistency in the themes grappled with in paratextual presentations across the decades but highlights how changing political priorities in particular could instigate discursive shifts. The project also highlights how the individual agency of marginal actors in the Chinese literary sphere (in the early period) and Black African writers (in the Maoist era) could also lead to translation activity. Ultimately, the project foregrounds the overwhelming determinism of non literary factors in the translation of Black literatures until the 1960s, when there is some evidence of an aesthetic appreciation of the works of Ousmane Sembène.
A thesis submitted in fulfilment of the requirements for the Doctor of Philosophy in African Literature to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, 2022